Influence of various thermal conditions on the composition of high‑temperature diffusion oxides (satellite inclusions) in solid steel - T. I. Sidorenko; E. V. Ermachenok; Yu. S. Belash (Литьë и металлургия)
The main goal of any modern production of long products is to ensure the required quality of finished products. One of the important quality indicators, along with mechanical and technological properties, is the quality of the rolled metal surface. The article presents the results of experimental studies of the composition of high‑temperature diffusion oxides formed on the surface of artificially deposited defects under various conditions of temperature exposure using the microrentgenospectral method on a scanning electron microscope with an energy dispersive microanalyzer. The characteristic features in terms of the percentage and presence of certain chemical elements in the scale of various steel grades have been established.